AB0177 Toll-like receptor 7(TLR7) is upregulated on peripheral b cells and associated with disease activity and damage in primary sjogren syndrome. (12th June 2018) - Xue, Y.; Wang, T.; Song, X.; Li, M.; Zeng, X.
Abstract : Objectives: Primary Sjogren Syndrom(pSS) is characterised by activitition of B cells, increased production of RNA-associated antibodies and elevated proportion of transitonal B cell. Toll-like receptors 7(TLR7) have been reported promoting the effects above in some murine models of SS. We took up this study to identify if TLR7 expression is associated with disease activity and the role of TLR7 in pSS. Methods: 21 pSS patients and 12 healthy controls(HCs) were selected. The mRNA expression of TLR7 was determined by real-time PCR on peripheral B cells of both pSS patients and HCs. We measured BAFF serum concentrations by ELISA, and the BAFF-R, TACI and BCMA expression was analysed on each B cell subset (CD27 - CD24 hi CD38 hi /transitional B cell; CD27 - CD24 lo CD38 lo /naive B cell;) by flow cytometry. The results were compared among patients with diversed degree of disease activity and damage to HCs. Results: The expression level of TLR7 mRNA were elevated in pSS patients compared with HCs(p=0.004), and correlated with the SSDAI (SS disease activity index) (r=0.803; p=0.009) and the SSDI(SS damage index)(r=0.881;p=0.002). Serum BAFF concentrations increased in pSS patients compared with HCs(p=0.041), but not corrleted with TLR7 expression. TACI expression in pSS patients in total B cells and traditional B cells compared to HCs were elevated and are both associated with TLR7 expression (r=0.763, p=0.048, r=0.820, p=0.004, respectively). A lower BAFFR expression was seen in transitional B cell compared with HCs(p=0.018). BCMA expression was of no significance. Conclusions: Increased TLR7 expression on peripheral B cells were associated with disease activity and damage, suggesting that TLR7 may play a role in the development in pSS. Increased serum BAFF concentrition and TACI expression were associated with TLR7 expression, indicating that BAFF may regulate TLR7 expression through TACI according to previous studies.TLR7 may be a potential treatment target of pSS and worth of further study. Disclosure of Interest: None declared